Hepatitis C virus eradication on glycemic control and insulin resistance - Carvalhal,Manuela Maria de Lima (2021)
SUMMARY OBJECTIVE: To review data regarding the effects of hepatitis C virus eradication on glycemic control and insulin resistance. METHODS: This is an integrative literature review, carried out in the PubMed, SciELO, and Lilacs databases. Studies published in the past five years that were fully available, written in English or Portuguese, and have addressed the effects of eradication of the hepatitis C virus on glycemic control and insulin resistance were selected. RESULTS: Nine studies were selected. Among the results found, it was observed that there is no consensus on the effects of viral eradication on glycemic control and IR, as some authors show an eventual improvement in insulin resistance and glycemic control, while other studies indicate that there are no significant differences between the parameters evaluated after viral eradication. CONCLUSIONS: Although there is a relationship between hepatitis C virus infection and the development of insulin resistance and type 2 diabetes mellitus and recent advances in research, it was observed that there is no consensus on improving insulin resistance and glycemic control after antiviral treatment, probably due to methodological differences between studies. However, it emphasizes the need to guide people diagnosed with hepatitis C, regarding changes in lifestyle, encouragement of multidisciplinary monitoring, and control of other risk factors.